THE DEVELOPMENT OF SCIENCE PRACTICUM MODULE INTEGRATED STEM ON BIOTECHNOLOGY TOPICS USING ETHNOSCIENCE APPROACH - Rafifah, Suci; Putri, Rahmah Evita (Department of Science Education, 2024)
One of the efforts made to overcome the problems contained in practicum activities in schools is to design and develop a science practicum module integrated STEM using ethnoscience approach. The STEM integrated practicum module is able to train student skills because students can experience the learning process directly. The use of the ethnoscience approach in the practicum module can introduce facts and phenomena that can be explained scientifically. In general, the aim of this research is to produce an science practicum module integrated STEM using ethnoscience approach that valid and practical to use. The type of research used is Research and Development (R&D). The research method used in the 3 stages of a the ADDIE, namely analysis, design, and development. The research instrument consisted of a validity and practicality test questionnaire. The results of the development stage indicate that the practicum module is valid with the validity test value given by the expert validator of 0,82. Practicum module in practical category with a questionnaire value of 0,89 teacher responses and 0,85 students responses. The results showed that science practicum module integrated STEM using ethnoscience approach can be used with valid and practical categories.